The Impact of Using Moodle in Teaching Islamic Education on the Immediate and Delayed Achievement for Female Students of Grade Nine and their Attitudes toward Moodle - Mohammed A. Alayasrah; Kareema A. Al Saadi (Sultan Qaboos University, 2016)
This study aimed to examine the impact of using Moodle in teaching Islamic education on the immediate and delayed achievement for female students of grade nine in Oman and their attitudes towards that. The sample consisted of 57 female students. divided into two groups: experimental (28), and control (29).The quasi. experimental design was used. To achieve the aims of the study, prepared achievement test consisted of (30) questions, and its content validity was investigated by a group of arbitrators. The reliability coefficient was (0.86). The prepared attitude scale towards Moodle and consisted of (22) items, and its content validity was investigated by a group of arbitrators, and the reliability coefficient was (0.80). The study concluded that there were significant statically differences at (0,05) between the degree mean of two groups of experimental and controlled, and on the immediate and delayed achievement test favoring experimental group. There were significant statically differences at (0,05) between the means of experimental group pre and post test favoring delayed application. The study recommended to using Moodle in teaching Islamic education since its effectiveness was proved on the immediate and delayed achievement and Positive effect of Attitudes.